Autoantibody prevalence in active tuberculosis: reactive or pathognomonic?. Issue 7 (25th July 2013) - Shen, Chieh-Yu; Hsieh, Song-Chou; Yu, Chia-Li; Wang, Jann-Yuan; Lee, Li-Na; Yu, Chong-Jen
Abstract : Objectives: To evaluate the autoantibody in patients without corresponding symptoms, whether these autoantibody are pathognomonic or not. We hypothesised that autoantibody may be reactive to chronic infection, such as tuberculosis (TB). Design: Randomised, case–control cohort study. Setting: A tertiary centre in Taiwan. Participants: We randomly chose 100 patients out of the data bank of patients with TB in a tertiary medical centre. All patients completed the sera sampling. We chose 100 patients according to autoantibody prevalence in previous literature. We also chose 100 medical staff as control group. Interventions: We tested anti-SSA, anti-SSB, anti-Sm, anti ribonucleoprotein, anti-Scl 70, anticentromere, anti-double-stranded DNA, anticardiolipin IgG and IgM in all patient and control groups. The clinical symptoms and the underlying disease were all recorded. Primary and secondary outcome measures: The result of sera antibody titre was recorded. For those with specific positive serology results, following examination was carried out after a 3-month anti-TB medication. Results: Anticardiolipin IgG titre was significantly higher in patients with TB than in control group. We compared the result with previous population study and found that anti-Scl70 is also significantly higher in patients with TB. The following up data in anti-Scl70 revealed decreased titre after treatment. No correlation between sera titre and clinical conditions was observed. Conclusions: In TB endemic areas, a significant proportion (32%) of patients with TB have elevated autoantibody titres, especially anticardiolipin IgG and anti-Scl-70. Mycobacterial studies should be performed in patients with elevated serum autoantibody titres but without the typical or multiple manifestations of autoimmune diseases. Trial registration: The study was approved by the Institutional Review Board of the hospital (NTUH REC: 9561707008) after informed consent had been obtained from the patients.